2015
DOI: 10.1007/s12103-015-9316-4
|View full text |Cite
|
Sign up to set email alerts
|

Police Body-Worn Cameras: Perceptions of Law Enforcement Leadership

Abstract: Many people are enthusiastic about the potential benefits of police body-worn cameras (BWC). Despite this enthusiasm, however, there has been no research on law enforcement command staff perceptions of BWCs. Given the importance that law enforcement leadership plays in the decision to adopt and implement BWCs, it is necessary to assess their perceptions. This is the first study to measure law enforcement leadership attitudes toward BWCs. The study relies on data collected from surveys administered to command s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 4 publications
5
106
0
Order By: Relevance
“…Despite methodological challenges, the findings from this body of work illuminate some themes for law enforcement and provoke hypotheses for further testing for researchers. For example, one consistent theme that has been reported in many of these studies is that once officers start using cameras, they feel positive (or at least neutral) about BWCs, or they become more positive about them over time (see, e.g., Ellis et al, 2015;Fouche, 2014;Grossmith et al, 2015;Jennings, Fridell, & Lynch, 2014;Jennings et al, 2015;Koen, 2016;McLean, Wolfe, Chrusciel, & Kaminski, 2015;Smykla et al, 2015;Toronto Police Service, 2016;. Additionally, have found that officer receptivity to BWCs may also be influenced by participating in shared events with other officers who are wearing BWCs.…”
Section: Officers' Attitudes Toward Body-worn Camerasmentioning
confidence: 82%
“…Despite methodological challenges, the findings from this body of work illuminate some themes for law enforcement and provoke hypotheses for further testing for researchers. For example, one consistent theme that has been reported in many of these studies is that once officers start using cameras, they feel positive (or at least neutral) about BWCs, or they become more positive about them over time (see, e.g., Ellis et al, 2015;Fouche, 2014;Grossmith et al, 2015;Jennings, Fridell, & Lynch, 2014;Jennings et al, 2015;Koen, 2016;McLean, Wolfe, Chrusciel, & Kaminski, 2015;Smykla et al, 2015;Toronto Police Service, 2016;. Additionally, have found that officer receptivity to BWCs may also be influenced by participating in shared events with other officers who are wearing BWCs.…”
Section: Officers' Attitudes Toward Body-worn Camerasmentioning
confidence: 82%
“…However, other studies have shown that police perceptions of BWV changed over time as officers reported growing familiarity with the technology and an appreciation for its benefits (Katz et al, 2014). A survey of law-enforcement command staff found that staff with less experience tended to be more sceptical than more experienced officers of the potential for BWV to make officers and communities safer, though both younger and older officers appreciated its benefits (Smykla et al, 2015). Other surveys found that a majority of officers are comfortable with the technology.…”
Section: Regulatory Applicationsmentioning
confidence: 99%
“…Accordingly, continuous filming policies, where BWCs are available, tend to be inconsistent with law enforcement "occupational culture," according to Hedberg et al (2017, p. 644). On the streets, this translates into officer concerns that BWCs could inhibit them from using necessary force, which would make them less safe (Smykla et al, 2016).…”
Section: Initial Law Enforcement Opposition To Bwcsmentioning
confidence: 99%
“…The purpose of this paper is to contribute to the empirical status of BWCs. Though previously explored in other scholarship (e.g., Gaub et al, 2017;Jennings, Fridell, & Lynch, 2014;Pelrey & Keener, 2016;Smykla et al, 2016), this examination differs by giving direct voice to officers on this issue. As part of a larger empirical endeavor on law enforcementarticulated strategies and views on policing gang violence, this subset of analyses presents officer insights on BWCs in a Southern American State.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation